Intra-incisional versus intravenous route of antibiotic administration in preventing surgical site infections: a randomized controlled trial - Patil, Aditya N.; Uppin, Veerendra M. (International Surgery Journal, 2018)
Background: Surgical site infection (SSI) is one of the most common postoperative complications following abdominal surgeries. Whilst the use of prophylactic antibiotics has been shown to reduce postoperative wound infection, controversy still remains as to the optimum route of administration and the duration of treatment. This study aims to compare the efficacy of a preoperative single dose of a cephalosporin antibiotic (cefotaxime) administered intraincisionally versus that administered intravenously, in preventing postoperative surgical site infections following appendicectomy. Methods: Sixty consecutive cases diagnosed as uncomplicated appendicitis who consented for open appendicectomy at a tertiary care institute were included in the study. Cases were randomized to 2 comparable groups of 30 patients each. Preoperatively, patients in Group A received a single dose of Inj. Cefotaxime 1g intraincisionally while those in Group B received the same intravenously. Incision sites were examined every alternative day starting on postoperative day 3 until removal of sutures. Signs of surgical site infection, if any, were recorded and outcomes were statistically tested for significance. Results: One patient in Group A (3.3%) and 4 patients in Group B (13.3%) showed signs of postoperative surgical site infection (p >0.05) during the follow up period which prolonged their hospital stay. Conclusions: This study showed that a single dose preoperative intraincisional administration of cefotaxime was as effective as intravenous administration for prevention of postoperative surgical site infection after open appendicectomy. Although the difference was not statistically significant, there was a reduced incidence of SSI in individuals who received intraincisional antibiotic. These results are encouraging for a way forward in reducing unnecessary burdening of systemic antibiotics in patients undergoing abdominal surgeries.